Analisis Hidrograf DAS Poso dengan Metode Hidrograf Satuan Sintetis Snyder dan Hidrograf Satuan Sintetis Soil Conversation Service (SCS) - Kahffi, A.; Lipu, S. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2021)
The Poso River is a river located in Poso Regency, Central Sulawesi Province, which has a length of 74.58 km, and watershed area of 1092.810 km2. Energy in the Poso River is used for hydroelectric power plant (PLTA). With the construction of the Poso hydropower plant, maximum flood discharge data is needed for the prevention of Poso hydro power plant safety. In calculating the flood discharge, the method used is a synthetic unit hydrograph. Synthetic unit hydrograph is a graph of the relationship between flow rate (Q) and time (t). In this study, the method used to calculate the designed flood discharge is the Snyder synthetic unit hydrograph method and the Soil Conversation Service (SCS) synthetic unit hydrograph. The aims of this study are to determine the largest flood discharge value and to determine the hydrograph shapes of the two methods. The parameters that will be obtained from both methods are peak time (Tp), base time (Tb) and peak discharge (Qp). From the analysis it can be found that in the Snyder SUH method, the peak time (Tp) is 12.616 hours, the base time (Tb) is 67.276 hours with a peak discharge (Qp) of 21.672 m3sec. Whereas in the SCS SUH method, the peak time (Tp) is 10.954 hours, the base time (Tb) is 57.268 hours with a peak discharge (Qp) of 20.751 m3/sec. The result demonstrates the result that the largest flood discharge has occurred in the Snyder SUH method.